Transitioning from club to national teams: Training and match load profiles of international footballers. Issue 8 (August 2019) - Noor, Denny; McCall, Alan; Jones, Mark; Duncan, Craig; Ehrmann, Fabian; Meyer, Tim; Duffield, Rob
Abstract: Objectives: To quantify and profile the training and match loads of international footballers as they transition from club-to-camp-to-tournament contexts during multiple international tournaments. Design: Retrospective single-cohort observational study. Methods: External (session duration and count) and internal (session Rating of Perceived Exertion [s-RPE]) load data of all outfield players from the same national team were compared between club, pre-tournament camp and initial tournament phases of 3 recent international competitions. Further, load profiles were compared between each phase based on the acute:chronic (A/C) ratio using a 7 to 21-day ratio. Results: Moderate-to-large effect sizes existed for increased number of sessions (ES = 1.92; 90% CI: 1.56, 2.27) and s-RPE training load (ES = 1.16; 0.84, 1.48) from club to camp. Conversely, transitioning from camp-to-tournament showed very large effects for decreased number of training sessions (ES = −3.17; −3.47, −2.86) and s-RPE training load (ES = −2.05; −2.35, −1.75), alongside increased number of matches (ES = 1.87; 1.55, 2.18) and s-RPE match load (ES = 1.57; 1.25, 1.89). Consequently, a moderate effect was evident for increased A/C ratio during the club-to-camp transition (ES = 1.02; 0.70, 1.33), while a moderate decrease in the A/C ratio occurred during the tournament (ES = −0.76; −1.06, −0.46). Conclusions: International footballers showed expected increased training load when entering into pre-tournament camps, predominately via increased number of training sessions. Subsequent reductions in training volume coincide with increased match volume, though total load decreases. Such profiles provide insight into load accumulation transitioning from club to national teams in international footballers.